1976
DOI: 10.1111/j.1432-1033.1976.tb10866.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Dimerization of the Variable Fragment of the Bence‐Jones Protein Au

Abstract: The dimerization of the variable fragment of the Bence-Jones protein Au was examined in phosphate buffers at pH 6.8 -6.9 and ionic strength of 0.1 M or 0.2 M at 20 "C. The dimerization constant was about 1 x 10' M-'. The reaction enthalpy was positive and the process was entropy driven. The association and dissociation rate constants were 9 x lo6 M-' s-' and 1.5 x lo2 s-l respectively. Temperature-jump experiments exhibited the presence of two isomers of the dimer, which are present at equilibrium in a ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The gel filtration chromatography ( Fig. 2A) showed that VL-1 and VL-2 are homodimers, which was generally observed for isolated VL domains (Maeda et al, 1976;Gavish et al, 1977;Azuma et al, 1978;Ionescu-Zanetti et al, 1999). Each protein was eluted as a single peak with an apparent molecular mass of 24.8 + 0.35 kDa (VL-1) or 26.5 + 0.42 kDa (VL-2).…”
Section: Vl-1 and Vl-2 Do Not Comprise Wrong Aggregates Non-native Dsupporting
confidence: 53%
“…The gel filtration chromatography ( Fig. 2A) showed that VL-1 and VL-2 are homodimers, which was generally observed for isolated VL domains (Maeda et al, 1976;Gavish et al, 1977;Azuma et al, 1978;Ionescu-Zanetti et al, 1999). Each protein was eluted as a single peak with an apparent molecular mass of 24.8 + 0.35 kDa (VL-1) or 26.5 + 0.42 kDa (VL-2).…”
Section: Vl-1 and Vl-2 Do Not Comprise Wrong Aggregates Non-native Dsupporting
confidence: 53%
“…The virtually identical primary structure of the CL portions of these proteins (and of the other K chains studied) implicates the VL portion of the polypeptide chain as the region responsible for the observed heterogeneity in self-association of light chains. The KDs of the native X chain TOD and the KI protein AU were slightly less than that of their respective VL-related fragments (24,28,32); the C domain therefore has little influence on the association of these light chains.…”
Section: Discussionmentioning
confidence: 97%
“…Under native conditions, the self-dissociation constant of LEN was determined to be 10 M at neutral pH (4). The importance of the variable domains in the association process of immunoglobulin light chains has long been recognized (5,6). Furthermore, the critical role in the association process of the Pro 96 of the CDR3 region of the variable domain has been demonstrated (7).…”
Section: Light Chain Amyloidosis Involves the Systemic Deposition Of mentioning
confidence: 99%